Peningkatan Konsep Pengukuran Pada Anak Usia 4-5 Tahun Menggunakan Media Donat Susun - Siti Salwa; Aisyah Amalia Khoirul Amini; Alfina Fatwa Khasanah; Lathipah Hasanah (Pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah dan Ilmu Keguruan, UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aims to validate that measurement methods in early childhood are very important, but many institutions do not apply this method. We are trying to use the medium of stacking to prove that the teaching of early childhood measurement is important to them. The main point of his research is children with problem solving, and also accurate donuts media as a teaching medium for measurements related to the size of the donut itself. And also the arrangement of such donuts from the largest to the smallest. The method we use is the class action method and the results of the research show that children aged 4-6 years are able to learn and understand the size of the stacking donut media, while for children aged 1-3 years still need direction and guidance on the commands from the stacking donut media.